Integrated bioinformatics analysis for novel miRNAs markers and ceRNA network in diabetic retinopathy - Li, Jingru; Li, Chaozhong; Zhao, Yulan; Wu, Xinyu; Yu, Shuai; Sun, Guihu; Ding, Peng; Lu, Si; Zhang, Lijiao; Yang, Ping; Peng, Yunzhu; Fu, Jingyun; et al. (Frontiers in Genetics, 2022)
In order to seek a more outstanding diagnosis and treatment of diabetic retinopathy (DR), we predicted the miRNA biomarkers of DR and explored the pathological mechanism of DR through bioinformatics analysis. Method: Based on public omics data and databases, we investigated ncRNA (non-coding RNA) functions based on the ceRNA hypothesis. Result: Among differentially expressed miRNAs (DE-miRNAs), hsa-miR-1179, -4797-3p and -665 may be diagnosis biomarkers of DR. Functional enrichment analysis revealed differentially expressed mRNAs (DE-mRNAs) enriched in mitochondrial transport, cellular respiration and energy derivation. 18 tissue/organ-specific expressed genes, 10 hub genes and gene cluster modules were identified. The ceRNA networks lncRNA FBXL19-AS1/miR-378f/MRPL39 and lncRNA UBL7-AS1/miR-378f/MRPL39 might be potential RNA regulatory pathways in DR. Conclusion: Differentially expressed hsa-miR-1179, -4797-3p and -665 can be used as powerful markers for DR diagnosis, and the ceRNA network: lncRNA FBXL19-AS1/UBL7-AS1-miR-378f-MRPL39 may represent an important regulatory role in DR progression.